2013
DOI: 10.1210/en.2013-1150
|View full text |Cite
|
Sign up to set email alerts
|

Mct8-Deficient Mice Have Increased Energy Expenditure and Reduced Fat Mass That Is Abrogated by Normalization of Serum T3 Levels

Abstract: Children with monocarboxylate transporter 8 (MCT8) deficiency lose weight, even when adequately nourished. Changes in serum markers of thyroid hormone (TH) action compatible with thyrotoxicosis suggested that this might be due to T3 excess in peripheral tissues. Mct8-deficient mice (Mct8KO) replicate the human thyroid phenotype and are thus suitable for metabolic studies so far unavailable in humans. In the current work, compared with wild-type (Wt) mice, Mct8KO mice were leaner due to reduced fat mass. They t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Mct8KO mice had decreased T4 and rT3 levels but increased TSH and slightly elevated T3 concentrations compared with WT mice ( Fig. 1 ), as reported previously ( 17 – 19 , 30 ). Consistent with previous data ( 19 ), Mct8D1D2KO mice had elevated T4, rT3, and TSH concentrations at all ages compared with WT and Mct8KO mice.…”
Section: Resultssupporting
confidence: 88%
“…Mct8KO mice had decreased T4 and rT3 levels but increased TSH and slightly elevated T3 concentrations compared with WT mice ( Fig. 1 ), as reported previously ( 17 – 19 , 30 ). Consistent with previous data ( 19 ), Mct8D1D2KO mice had elevated T4, rT3, and TSH concentrations at all ages compared with WT and Mct8KO mice.…”
Section: Resultssupporting
confidence: 88%
“…Cosmo et al reported that TH uptake by skeletal muscle can occur independently of monocarboxylate transporter 8 (Mct8). However, they found enhanced TH action, T 3 content, and glucose metabolism in Mct8 knockout mice [32]. We speculate that TTR might maintain the TH content in Mct8 knockout mice and, hence, normal muscle metabolism and development.…”
Section: Discussionmentioning
confidence: 71%
“…These efforts were severely hampered by the fact that information regarding molecular and cellular abnormalities in the CNS of affected patients are still scarce, and that a suitable animal model replicating the phenotype of human MCT8 deficiency was not available. Although mice deficient in MCT8 revealed important aspects regarding the role of MCT8 in peripheral tissues, such as liver, kidneys, and thyroid gland (11)(12)(13)(31)(32)(33), Mct8 KO mice did not show any overt neurological symptoms, calling this mouse model into question as an adequate model system for AHDS.…”
Section: Discussionmentioning
confidence: 99%